Datasets of meteorological drought events and risks for the developing countries in Eurasia. Issue 2 (2nd April 2020) - Zhong, Linhao; Hua, Lijuan; Yan, Zhongwei
ABSTRACT: For the area of Eurasia concentrated with developing countries (referred to here by the abbreviation DPEA), mainly located in Asia and Eastern Europe, this work presents datasets of gridded meteorological drought events and country-based drought risk by combining multiple drought indices and socio-economic data. A basic gridded dataset of the drought events during 1950–2015 is extracted from three drought indices: the self-calibrating Palmer Drought Severity Index, the Standardized Precipitation Index, and the Standardized Precipitation Evapotranspiration Index. The three drought indices generally show consistent characteristics of drought events in DPEA. A second-level dataset (a drought risk dataset) is then produced as the product of drought hazard, exposure and vulnerability during 2000–2015. For drought exposure, the indicators of population and livestock density, agricultural land and water stress are chosen, while drought vulnerability composites multiple social, economic and infrastructural factors. Drought hazard tends to concentrate at the southern rim of Eurasia. Relatively large differences in drought exposure exist between different countries, but for drought vulnerability the differences are small. After considering the socio-economic components in risk assessment, most countries in West, South-Central and South Asia have the highest drought risk in DPEA. The datasets of drought events and risks are available at http://www.dx.doi.org/10.11922/sciencedb.898 .